1979
DOI: 10.1001/jama.1979.03290450037021
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Failure in Cancer Patients

Abstract: A review of 180 cancer patients requiring mechanical ventilation disclosed that 26% survived to extubation, and 13% and 7% were alive at two and six months, respectively. Mortality was related to several factors individually and the cumulative number of organ systems dysfunctioning in a given patient. Compared with general intensive care patients, those with respiratory failure and neoplastic disease demonstrated a high incidence of drug-induced pulmonary disease, hematologic abnormalities, pneumothorax, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…7 • 1 x With some exceptions, 2 most studies indicate that the underlying diagnosis does affect survival following MV.· 12 ··1fi In general, most studies indicate good survival in patients with COPD and poor survival in those with ARDS, AIDS, hematologic malignancy, and lung cancer. 37 We found that survival was significantly predicted by duration of MV only at the interval of hospital discharge. Two earlier reports failed to show that duration of MV distinguishes survivors from nonsurvivors at hospital dischargeYJ.> Overall survival between initiation of MV and I year after hospital discharge was not affected by duration of MV (proportional hazards regression).…”
Section: Discussionmentioning
confidence: 62%
“…7 • 1 x With some exceptions, 2 most studies indicate that the underlying diagnosis does affect survival following MV.· 12 ··1fi In general, most studies indicate good survival in patients with COPD and poor survival in those with ARDS, AIDS, hematologic malignancy, and lung cancer. 37 We found that survival was significantly predicted by duration of MV only at the interval of hospital discharge. Two earlier reports failed to show that duration of MV distinguishes survivors from nonsurvivors at hospital dischargeYJ.> Overall survival between initiation of MV and I year after hospital discharge was not affected by duration of MV (proportional hazards regression).…”
Section: Discussionmentioning
confidence: 62%